2016
DOI: 10.1080/10410236.2015.1082456
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Pilot Intervention to Increase Physician–Patient Communication About Stroke Risk in Indonesia

Abstract: In Indonesia, where stroke is the leading cause of death, we designed and tested a brief intervention to increase physician-patient conversations about stroke prevention in community health centers. The pilot study used a quasi-experimental design involving repeated cross-sectional data collection over 15 weeks to compare pre- and during-intervention differences within four centers. We conducted exit interviews with 675 patients immediately following their medical appointments to assess whether physicians disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Consequently, they were often overburdened with a large number of patients, which may lead to limited time spent talking to the patients. 52 Therefore, initiating collaboration with community pharmacists for managing chronic illnesses is necessary to provide more detailed information and monitor the outcomes of people with diabetes. Medication Therapy Management (MTM) is pharmacist-led professional services that have been implemented for diabetes management worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they were often overburdened with a large number of patients, which may lead to limited time spent talking to the patients. 52 Therefore, initiating collaboration with community pharmacists for managing chronic illnesses is necessary to provide more detailed information and monitor the outcomes of people with diabetes. Medication Therapy Management (MTM) is pharmacist-led professional services that have been implemented for diabetes management worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…POSBINDU-PTM is expected to be able to conduct periodic health checks once a month. A pilot project has shown that a brief intervention to motivate physician-patient conversations about stroke prevention may improve these conversations in community health centers [ 17 ]. The third effort is a curative action by strengthening health services and increasing human resources.…”
Section: Government and Nongovernment Actionsmentioning
confidence: 99%